Teachers’ Readiness towards the Integration of Information and Communications Technology in Teaching and Learning of Engineering Graphics and Design in KwaZulu-Natal - Philani Brian Mlambo; Mogale Simon Albert Maeko; Samuel Dumazi Khoza (Research in Social Sciences and Technology, 2023)
The integration of information and communications technology (ICT) into the education system has led to changes in the way teaching and learning are conducted. These changes have necessitated the need for teachers to have ICT skills that would help them integrate ICT into teaching and learning (T&L). Hence, this qualitative study was conducted to investigate the state of readiness of Engineering Graphics and Design (EGD) teachers in the integration of ICT in T&L in uMgungundlovu secondary schools. Convenience sampling was employed to select nine EGD teachers to partake in this study. Semi-structured interviews and classroom observations were used to collect data. Data gathered from interviews was subjected to thematic analysis, and data gathered from observations was reported descriptively. The findings of this study revealed that EGD teachers in uMgungundlovu District are ready to integrate ICT into the T&L of EGD, as they indicated that ICT integration in EGD lessons is essential. The study further revealed a shortage of ICT resources and a lack of ICT skills among teachers, which hinder the successful integration of ICT. The study recommends that the Department of Basic Education (DBE) provide teachers with ICT training so that those who are technically disadvantaged can be equipped with relevant ICT skills. The study further recommends that DBE give the schools an AutoCAD license, as it has been proven to be a useful ICT tool.